bookshelf/Common/Real/Sequence.tex

133 lines
4.2 KiB
TeX
Raw Normal View History

\documentclass{article}
\input{../../preamble}
\makecode{../..}
\begin{document}
\header{Sequences}{}
\tableofcontents
\section{Summations}%
\hyperlabel{sec:summations}
\subsection{\verified{Arithmetic Series}}%
\hyperlabel{sub:sum-arithmetic-series}
2023-08-09 13:39:41 +00:00
Let $(a_i)_{i \geq 0}$ be an arithmetic sequence with common difference $d$.
Then for some $n \in \mathbb{N}$,
\begin{equation}
\hyperlabel{sub:sum-arithmetic-series-eq1}
\sum_{i=0}^n a_i = \frac{(n + 1)(a_0 + a_n)}{2}.
\end{equation}
\code{Common/Real/Sequence/Arithmetic}
{Real.Arithmetic.sum\_recursive\_closed}
2023-08-09 13:39:41 +00:00
\begin{proof}
Let $(a_i)_{i \geq 0}$ be an arithmetic sequence with common difference $d$.
By definition, for all $k \in \mathbb{N}$,
\begin{equation}
\hyperlabel{sub:sum-arithmetic-series-eq2}
a_k = (a_0 + kd).
\end{equation}
Define predicate $P(n)$ as "identity \eqref{sub:sum-arithmetic-series-eq1}
holds for value $n$."
We use induction to prove $P(n)$ holds for all $n \geq 0$.
\paragraph{Base Case}%
Let $k = 0$.
Then $$\sum_{i=0}^k a_i = a_0 = \frac{2a_0}{2} =
\frac{(k + 1)(a_0 + a_k)}{2}.$$
Therefore $P(0)$ holds.
\paragraph{Induction Step}%
Assume induction hypothesis $P(k)$ holds for some $k \geq 0$.
Then
\begin{align*}
\sum_{i=0}^{k+1} a_i
& = \sum_{i=0}^k a_i + a_{k+1} \\
& = \frac{(k + 1)(a_0 + a_k)}{2} + a_{k+1}
& \text{induction hypothesis} \\
& = \frac{(k + 1)(a_0 + (a_0 + kd))}{2} + (a_0 + (k + 1)d)
& \eqref{sub:sum-arithmetic-series-eq2} \\
& = \frac{(k + 1)(2a_0 + kd)}{2} + (a_0 + (k + 1)d) \\
& = \frac{(k + 1)(2a_0 + kd) + 2a_0 + 2(k + 1)d}{2} \\
& = \frac{2ka_0 + k^2d + 4a_0 + kd + 2kd + 2d}{2} \\
& = \frac{(k + 2)(2a_0 + kd + d)}{2} \\
& = \frac{(k + 2)(a_0 + a_0 + (k + 1)d)}{2} \\
& = \frac{(k + 2)(a_0 + a_{k+1})}{2}
& \eqref{sub:sum-arithmetic-series-eq2} \\
& = \frac{((k + 1) + 1)(a_0 + a_{k+1})}{2}.
\end{align*}
Thus $P(k)$ implies $P(k + 1)$ holds true.
\paragraph{Conclusion}%
By mathematical induction, it follows for all $n \geq 0$, $P(n)$ is true.
\end{proof}
\subsection{\verified{Geometric Series}}%
\hyperlabel{sub:sum-geometric-series}
2023-08-09 13:39:41 +00:00
Let $(a_i)_{i \geq 0}$ be a geometric sequence with common ratio $r \neq 1$.
Then for some $n \in \mathbb{N}$,
\begin{equation}
\hyperlabel{sub:sum-geometric-series-eq1}
\sum_{i=0}^n a_i = \frac{a_0(1 - r^{n+1})}{1 - r}.
\end{equation}
\code{Common/Real/Sequence/Geometric}
{Real.Geometric.sum\_recursive\_closed}
2023-08-09 13:39:41 +00:00
\begin{proof}
Let $(a_i)_{i \geq 0}$ be a geometric sequence with common ratio $r \neq 1$.
By definition, for all $k \in \mathbb{N}$,
\begin{equation}
\hyperlabel{sub:sum-geometric-series-eq2}
a_k = a_0r^k.
\end{equation}
Define predicate $P(n)$ as "identity \eqref{sub:sum-geometric-series-eq1}
holds for value $n$."
We use induction to prove $P(n)$ holds for all $n \geq 0$.
\paragraph{Base Case}%
Let $k = 0$.
Then $$\sum_{i=0}^k a_i = a_0 = \frac{a_0(1 - r)}{1 - r} =
\frac{a_0(1 - r^{k+1})}{1 - r}$$
Therefore $P(0)$ holds.
\paragraph{Induction Step}%
Assume induction hypothesis $P(k)$ holds for some $k \geq 0$.
Then
\begin{align*}
\sum_{i=0}^{k+1} a_i
& = \sum_{i=0}^k a_i + a_{k+1} \\
& = \frac{a_0(1 - r^{k+1})}{1 - r} + a_{k + 1}
& \text{induction hypothesis} \\
& = \frac{a_0(1 - r^{k+1})}{1 - r} + a_0r^{k + 1}
& \eqref{sub:sum-geometric-series-eq2} \\
& = \frac{a_0(1 - r^{k+1}) + a_0r^{k+1}(1 - r)}{1 - r} \\
& = \frac{a_0(1 - r^{k+1} + r^{k+1}(1 - r))}{1 - r} \\
& = \frac{a_0(1 - r^{k+1} + r^{k+1} - r^{k+2})}{1 - r} \\
& = \frac{a_0(1 - r^{k+2})}{1 - r} \\
& = \frac{a_0(1 - r^{(k + 1) + 1})}{1 - r}.
\end{align*}
Thus $P(k)$ implies $P(k + 1)$ holds true.
\paragraph{Conclusion}%
By mathematical induction, it follows for all $n \geq 0$, $P(n)$ is true.
\end{proof}
\end{document}